Deregulation of miR-92a expression is implicated in hepatocellular carcinoma development - Shigoka, Masatoshi; Tsuchida, Akihiko; Matsudo, Takaaki; Nagakawa, Yuichi; Saito, Hitoshi; Suzuki, Yoshiaki; Aoki, Tatsuya; Murakami, Yoshiki; Toyoda, Hidenori; Kumada, Takashi; Bartenschlager, Ralf; Kato, Nobuyuki; et al. (Pathology international, 2010)
MicroRNAs (miRNAs) belong to a class of the endogenously expressed non-coding small RNAs which primarily function as gene regulators. Growing evidence suggests that miRNAs have a significant role in tumor development and may constitute robust biomarkers for cancer diagnosis and prognosis. The miR-17-92 cluster especially is markedly overexpressed in several cancers, and is associated with the cancer development and progression. In this study, we have demonstrated that miR-92a is highly expressed in hepatocellular carcinoma (HCC). In addition, the proliferation of HCC-derived cell lines was enhanced by miR-92a and inhibited by the anti-miR-92a antagomir. On the other hand, we have found that the relative amount of miR-92a in the plasmas from HCC patients is decreased compared with that from the healthy donors. Interestingly, the amount of miR-92a was elevated after surgical treatment. Thus, although the physiological significance of the decrease of miR-92a in plasma is still unknown, deregulation of miR-92 expression in cells and plasma should be implicated in the development of HCC.
Gesehen am 17.07.2023